2010
DOI: 10.1002/dvdy.22256
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects and impaired neural progenitor cell proliferation in Gβ1‐deficient mice

Abstract: Heterotrimeric G proteins are well known for their roles in signal transduction downstream of G protein–coupled receptors (GPCRs), and both Gα subunits and tightly associated Gβγ subunits regulate downstream effector molecules. Compared to Gα subunits, the physiological roles of individual Gβ and Gγ subunits are poorly understood. In this study, we generated mice deficient in the Gβ1 gene and found that Gβ1 is required for neural tube closure, neural progenitor cell proliferation, and neonatal development. Abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…To date, of the four similar Gb subunits, only Gb 1 has been knocked out in mice. Interestingly, 40% of Gb 1 2/2 mice exhibit neural tube defects resulting in embryonic lethality, whereas the knockout mice that do not exhibit this phenotype develop microencephaly and die perinatally (Okae and Iwakura, 2010). Additional defects in Gb 1 2/2 mice without neural tube defects include abnormal suckling behavior and respiratory defects.…”
Section: Phenotypes Associated With Knockout and Knockdown Of Gb mentioning
confidence: 99%
“…To date, of the four similar Gb subunits, only Gb 1 has been knocked out in mice. Interestingly, 40% of Gb 1 2/2 mice exhibit neural tube defects resulting in embryonic lethality, whereas the knockout mice that do not exhibit this phenotype develop microencephaly and die perinatally (Okae and Iwakura, 2010). Additional defects in Gb 1 2/2 mice without neural tube defects include abnormal suckling behavior and respiratory defects.…”
Section: Phenotypes Associated With Knockout and Knockdown Of Gb mentioning
confidence: 99%
“…Although a number of studies have also examined the specific roles of individual Gβ and Gγ subunits, we still do not have a clear view of their individual functions. Functions for individual Gβ and Gγ subunits have been attributed using antisense approaches and the roles they play in receptor signalling pathways as well as embryonic development have been characterized in animal knockout models [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Gβ [1][2][3][4] subunits share 78-88% identity over their approximately 340 amino acid sequences (reviewed in [2,19]).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of Gβγ in neuronal development and differentiation has been previously shown [68,89]. Gβ1-deficient mice have been shown to have neural tube defects [94], and Gβ5-knockout mice have been shown to display abnormal behavior and develop multiple brain abnormalities [95]. It has also been shown that impaired Gβγ signaling promotes neurogenesis in the developing neocortex and increased neuronal differentiation of progenitor cells [68].…”
Section: G Protein-microtubule Interactions and Neuronal Differentiationmentioning
confidence: 93%
“…More recently, using biochemical and immunofluorescence analysis, it has been demonstrated that Gβγ-MT interactions and modulation of MT assembly is critical for NGF-induced neuronal differentiation of PC12 cells [94]. To address this, PC12 cells were treated with NGF over the course of three days to allow for neuronal differentiation.…”
Section: G Protein-microtubule Interactions and Neuronal Differentiationmentioning
confidence: 99%
See 1 more Smart Citation